Question Types and Questioning Tactics Used by Bright English Teacher during English Online Class - Wijaya Wijaya; Henny Putri Saking Wijaya (Kata Kita: Journal of Language, Literature, and Teaching, 2022)
This study was conducted to determine what question types and questioning tactics the Bright English language teacher used in English online classes. In this study, the writers used Wragg and Brown’s (2001) theory of three question types and seven questioning tactics to analyze the data. This study was done using a qualitative approach. The findings showed that the teacher asked conceptual and empirical questions to students in online meetings. When asking questions, the teacher employed five questioning tactics: pausing and pacing, directing and distributing, listening to replies and responding, prompting and probing, and sequencing questions. In conclusion, the teacher's question types and questioning tactics were affected by the lesson’s topic and the class situation. For further research, the writers suggested that two or more learning groups with students from different grades could be analyzed in onsite and online learning environments.